Unraveling the Materiality Analysis of the Brazilian Health Industry Players: Proposal of a Reference Table - Hong Yuh Ching (Journal of Management Research, 2024)
The current study proposes a practical and structured approach for performing materiality analysis that results in a reference table with 8 dimensions and 13 material topics. The models of SASB Standards and Sustainable Development Goals as well as requirements of the health industry key players were used as references for this reference table. The key players were divided into producers, intermediaries, and providers besides the regulatory agency. This reference model takes into account a breakdown of the dimensions and topics that are transversal to all groups of players and classifies those that have an impact and are relevant under each group of players. In unraveling the materiality analysis of Brazilian health industry players, it becomes evident that success in this competitive landscape requires a holistic understanding of factors influencing decision-making. The contribution of this article is to delve into the intricate details of the materiality analysis, shedding light on its significance and impact within the Brazilian health industry.